2019
DOI: 10.1038/s41598-019-54705-x
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 promotes migration and invasion in head and neck squamous cell carcinoma by upregulating TGF-β1/Smad2/3 signaling

Abstract: The chemokine receptor CXCR7 has been suggested to play important roles in the progression of several types of cancers. However, few studies have investigated the biological roles of CXCR7 in head and neck squamous cell carcinoma (HNSCC). CXCR7 expression and its clinical implications were examined in 103 HNSCC tissues using immunohistochemistry (IHC). The biological roles and mechanisms of CXCR7-mediated signaling pathways were investigated in HNSCC cells through CXCR7 overexpression in vitro and in vivo. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 45 publications
(46 reference statements)
1
38
0
Order By: Relevance
“…The activation of CXCR7 by its ligand CXCL12 could promote cell migration, angiogenesis, tumorigenesis, invasion, metastasis and anti-apoptosis [25]. CXCR7 is considered to be an EMT-related gene and is highly expressed in various cancer cells [26][27][28][29][30][31]. It was shown to be involved in the regulation of several pathways in cancer cells such as TGF-β1/Smad2/3 [30], PI3K/Akt [32] and β-arrestin [33] signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of CXCR7 by its ligand CXCL12 could promote cell migration, angiogenesis, tumorigenesis, invasion, metastasis and anti-apoptosis [25]. CXCR7 is considered to be an EMT-related gene and is highly expressed in various cancer cells [26][27][28][29][30][31]. It was shown to be involved in the regulation of several pathways in cancer cells such as TGF-β1/Smad2/3 [30], PI3K/Akt [32] and β-arrestin [33] signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…EMT enhances cell motility and helps the release of breast cancer cells from the primary tumor and the establishment of metastatic colonies at distant sites [40]. Previous studies have reported that CXCR7 promotes EMT by upregulating TGF-β1 [28][29][30]. We determined the expression levels of EMT-related genes in SOX4-expressing cells and found that the expression of three mesenchyme markers Vimentin, N-cadherin, and Fibronectin were upregulated, and that of the epithelial marker E-cadherin was downregulated.…”
Section: Discussionmentioning
confidence: 93%
“…The activation of CXCR7 by its ligand CXCL12 could promote cell migration, angiogenesis, tumorigenesis, invasion, metastasis and antiapoptosis [24]. CXCR7 is considered to be an EMT-related gene and is highly expressed in various cancer cells [25][26][27][28][29][30]. However, the effect of CXCR7 on distant metastasis of breast cancer remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, lipopolysaccharide induces the TLR4 (toll-like receptor 4)/MD-2 (myeloid differential protein-2) pathway, which leads to the upregulation of CXCR7, and ultimately tumor growth and metastasis [57]. CXCR7 regulates transforming growth factor-β1 (TGF-β1)/Smad2/3 signaling in head and neck squamous cell carcinoma [58]. Both the receptor and CXCL11 are present at higher levels in hepatocellular carcinoma (HCC) than in healthy livers in both mice and humans [3].…”
Section: The Role Of Cxcr7 In Cancersmentioning
confidence: 99%